Geothermal energy : silica precipitation and utilization - Aníta Hauksdóttir 1990- (2016)
Silica precipitation experiments have been ongoing at the Reykjanes geothermal power plant, Iceland, since 2011. Silica samples were obtained from the field and thoroughly investigated to estimate the silica’s potential as a marketable product. Targeted applications were studied in detail and the main characteristics and properties of silica used for these applications identified. The analysis of the Reykjanes silica indicates some possibilities of producing a marketable silica from the geothermal field. SEM images of all samples revealed spherical particles of various sizes. Both SEM and EDX analysis give some indications that modifying the precipitation process can affect the chemical composition and the particle size and surface. Recirculation in the precipitation process might produce silica particles with a rougher surface and smaller particle sizes. The main impurities are salts, likely from the saltwater solution (the Reykjanes brine) that the silica precipitates from. Potassium was detected at very low concentrations according to the EDX. In two of the three samples, Manganese and Iron were also detected at low concentrations. A number-based particle size distribution gave an average particle size of about 2.4 μm, and a volume based particle size distribution gave an average particle size of 21.1 μm. The relatively broad particle size distribution is somewhat undesired, but the raw silica sludge could easily be processed further, where it could be both filtered and washed, giving a purer product with a narrower size distribution. The silica is porous with a broad pore size distribution, ranging from 0.1-400 μm and oil absorption was in the range between 147-158 grams oil per 100 grams of sample. This would be considered low to medium absorption capacity, but there are some applications where this fits quite nicely. The main marketing obstacle of the Reykjanes silica is the low specific surface area but the nitrogen adsorption investigation revealed a BET of only 4.4 m2 g−1, which is considerably lower ...